Postmoderni pristopi v ekonomski geografiji - Kušar, Simon (Geografski vestnik, 2010)
Institutional approach in economic geography is a result of the institutional turn in social sciences. This approach highlights the importance of formal and informal institutions for the development of economy: spatial variations of institution performances lead to inter-regional disparities. Although the institutional approach in economic geography experiences many theoretical and methodological difficulties, it proved very useful as a theoretical-methodological background for analysing the role of planning at locating production facilities in Slovenia. Institutional turn was noticed also in Slovenian economic geography, but until now the theoretical concepts were not presented and used thoroughly.
Keywords: ekonomska geografija; ekonomski razvoj; regionalni razvoj